Pragmatic Foundations in Arabic Proverbs: Reading Jamharat al-Amthal by Abu Hilal AlAskari (مجلة إحالات, 2026)
This research aims atclarifying somefeatures of Pragmaticmeditation in proverbliterature inthe book "JamharatAl'Amthal" composed by "AbuHilal Al-Askary" (310 H). This research focusedon the most important concept and foundation developed in the western Pragmatic study such as:the concept of linguistic usage, speech act, context, principle of Speech cooperationand intention.This research also studied the clarification of proverb concept and its literarycategory andposition, and its importance as it was clarified by Arabic culture and heritage. Thisresearch provedthat Abu Hilal Al-Askary'sthought and studyof proverbs contain indicationsand featureswhich givea firm consolidation to numerous pragmatic concepts and rules in the Western study.